2013
DOI: 10.1080/14786419.2012.733387
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profile and biological activities ofDeguelia duckeanaA.M.G. Azevedo (Fabaceae)

Abstract: Deguelia duckeana is popularly known as timbó and used by indigenous people as ictiotoxic. On account of there being no literature pertaining to the chemical profile or biological activity of this plant, the hexane, methanol and aqueous crude extracts from leaves, stems and roots were assayed that presented very high cytotoxic potential against Artemia salina, achieving 100% mortality in up to 5.0 µg mL(-1) concentration, but lower antioxidant potential on 2,2-diphenyl-1-picryl-hydrazyl and Fe(3+)/Phenanthroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Compound 1 (1.2 g) was isolated from these subfractions. This compound was identified as lonchocarpine by instrumental analysis and compared to an authentic standard described in the literature (Lima et al ., 2013). The purity of lonchocarpine was more than 95%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 (1.2 g) was isolated from these subfractions. This compound was identified as lonchocarpine by instrumental analysis and compared to an authentic standard described in the literature (Lima et al ., 2013). The purity of lonchocarpine was more than 95%.…”
Section: Methodsmentioning
confidence: 99%
“…It also showed acute anti-inflammatory and anti-oedematogenic properties in a paw oedema model (Fontenele et al ., 2009). In addition, lonchocarpine has anti-bacterial activity on Staphylococcus aureus (Lima et al , 2013). A recent study reported that lonchocarpine inhibited nitric oxide production in lipopolysaccharidestimulated BV2 microglial cells (Li et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on 1 H-, 13 C-NMR and EI-MS data as well as comparison to spectral data from the literature these compounds were identified as 3,5,4'-trimethoxy-4-prenylstilbene (1) [11], 4-methoxyderricidine (2) [11], 4-hydroxylonchocarpine (4) [11], 4-methoxylonchocarpine (5) [11], 4'-hydroxyisolonchocarpine (7) [12], 4'-methoxyisolonchocarpine (8) [13], 3',4'-methylenedioxy-7-methoxyflavone (10) [14] and 2,2-dimethylchromone-5,4'-dihydroxy-5'-methoxyflavone (11) [15]. The hexane extract from branches yielded two known flavonoids which were identified by the methods mentioned above as lonchocarpine (3) [11] and 3',4',7-trimethoxyflavone (9) [16].…”
Section: Isolation and Identification Of Flavonoids From D Duckeana mentioning
confidence: 99%
“…The hexane extract from branches yielded two known flavonoids which were identified by the methods mentioned above as lonchocarpine (3) [11] and 3',4',7-trimethoxyflavone (9) [16]. Except for 1, 3, and 4 [11] all these compounds are described for the first time in D. duckeana. The structures are given in Figure 1.…”
Section: Isolation and Identification Of Flavonoids From D Duckeana mentioning
confidence: 99%
See 1 more Smart Citation